BLUETOOTH HEADPHONES TO REDUCE STRESS WITH A VIRTUAL ASSISTANT FOR UNIVERSITY STUDENTS - Mamani Machaca, Elizabeth-Susan; Chata-Aquino, Alvaro; Cuba-Herrera, Gabriel; Fernández-Arenas, Luis; Montoya-Rodriguez, Sebastian; Esquicha-Larico, Elias; Cuya-Zevallos, Carla (LACCEI, 2025)
Chronic and acute stress has negative impacts on mental health, immune system and general well-being and is a risk factor for cardiovascular diseases and mood disorders. Although psychological and pharmacological therapy are common, such solutions are also not always available permanently and with real-time adjustment to the subject's state and, therefore, their efficacy in daily scenarios is restricted. To address this problem, this research presents an auditory device that will combine continuous monitoring of signs of stress, stimulation to the vagus nerve and adaptive responses (soothing music, vibrations) to automatically respond to physiological indicators of stress. The closed-loop system will allow for personalized and continuous intervention, in contrast to traditional passive approaches to stress management. The proposed project seeks to integrate the device with university students to improve academic, social and emotional performance, obtaining a 74% acceptance and approval level from our target audience.